“Choices? That's the dream”: challenges and opportunities in non-speech information closed-captioning - May, Lloyd; Clemens, Michael; Dang, Khang; Ohshiro, Keita; Sridhar, Sripathi; Wee, Pauline; Fuentes, Magdalena; Lee, Sooyeon; Cartwright, Mark (Frontiers in Computer Science, 2025)
IntroductionAccess to non-speech information (NSI) in video content is essential to creating accessible and engaging video content, particularly for D/deaf and Hard-of-Hearing (DHH) audiences. In this paper we present an overview of the current state of NSI captioning research, professional practice, and user preferences.MethodsWe utilized a comprehensive review approach that combined a systematic literature review methodology with a mixed-methods survey and interview study. 1276 papers were screened with 36 eligible for the final inductive best fit analysis. 168 DHH participants completed an online survey and 15 participated in semi-structured interviews. Additionally, 5 professional captioners participated in semi-structured interviews.Results and discussionWe offer systematic insights into the current challenges related to NSI captioning faced by DHH users and professional captioners, trends in recent NSI captioning research, as well as opportunities for future work that enhance user agency, utilize integrated research methodologies, and broaden community involvement.